Promoting the quality of human resource training in the logistics industry in Vietnam - Le, Thi Hai Duong; Phan, Le Ngoc Chau (Tạp Chí Khoa Học Và Công Nghệ Trường Đại Học Bình Dương, 2024)
The logistics industry is gradually becoming successful and attracting a large number of resources, especially young people. However, up to now, the provision of resources for the logistics industry is considered a wave of globalization in general and Vietnam in particular, which is still attracting a large number of resources. The quality of training is positively influenced by factors related to the teaching staff (teaching qualifications - expertise, understanding the training needs of businesses, the teaching staff cares about the training needs of businesses, good communication skills, using modern teaching methods) of the teaching staff and the training program (clear output standards, regularly updated programs, the school arranges - allocates the modules in the training program reasonably, diverse and rich elective subjects) to meet the development. Therefore, promoting the training of quality human resources in the logistics industry in Vietnam is very necessary today.